The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00167-011-1593-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patellar retention versus resurfacing in LCS mobile-bearing total knee arthroplasty

Abstract: Therapeutic, retrospective, comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
(67 reference statements)
1
21
0
Order By: Relevance
“…And the latest study of Pavlou et al [29] provided further findings that neither patellar resurfacing nor the prosthetic design affects the clinical results of TKAs. Studies of LCS mobile-bearing total knee arthroplasty [30,31] showed the importance of soft tissue, especially the ligaments, in the decision for patellar resurfacing or not. Hwang et al [31] concluded that if soft tissue balancing and a patella-friendly prosthetic design are properly used, patellar retention with a patelloplasty might be viable, even in knees with serious patellofemoral arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the latest study of Pavlou et al [29] provided further findings that neither patellar resurfacing nor the prosthetic design affects the clinical results of TKAs. Studies of LCS mobile-bearing total knee arthroplasty [30,31] showed the importance of soft tissue, especially the ligaments, in the decision for patellar resurfacing or not. Hwang et al [31] concluded that if soft tissue balancing and a patella-friendly prosthetic design are properly used, patellar retention with a patelloplasty might be viable, even in knees with serious patellofemoral arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of LCS mobile-bearing total knee arthroplasty [30,31] showed the importance of soft tissue, especially the ligaments, in the decision for patellar resurfacing or not. Hwang et al [31] concluded that if soft tissue balancing and a patella-friendly prosthetic design are properly used, patellar retention with a patelloplasty might be viable, even in knees with serious patellofemoral arthritis. Since there have been no final conclusions about resurfacing of patella or not during TKA, more studies are needed to be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In case the patella remains un-resurfaced, the proper selection of prosthetic design, using a patella-friendly femoral component has proven to be extremely important [34][35][36][37][38][39][40]. The supporters of the non-resurfacing strategy prefer to attempt to provide a a better accommodation with the native patella femoral components, using an anatomically shaped trochlear configuration.…”
Section: Discussionmentioning
confidence: 99%
“…In the 10-year follow-up data of 600 unresurfaced TKAs using a "patella-friendly" design, O'Brien et al [61] found significant anterior knee pain in only 1.5 % of cases requiring secondary resurfacing and concluded that when using a patella friendly design, leaving the patellae unresurfaced does not adversely affect the outcome. In a more recent study, Hwang et al [62] compared the 7-year results of 2 groups of patients receiving patella-friendly designs. The authors were unable to detect any significant differences in anterior knee pain or revision rates between unresurfaced and resurfaced knees.…”
Section: Clinical Outcomesmentioning
confidence: 99%